وسائل التعليم "فلانيل بوارد" (Flannel Board) لترقية المهارة الكتابة - Salik, Mohammad; Syafi'i; A’yun, Risa Qurrota; Amalia, Yasmin Firda (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
The research was conducted because of problems related to how the application, efficiency and effectiveness of the Flannel Board learning media to improve the writing skills of seventh graders at the Billingual Terpadu Junior High School Krian Sidoarjo to determine the application, efficiency and effectiveness of the Flannel Board learning media to improve the writing skills of seventh graders at Billingual Junior High School Terpadu Krian Sidoarjo Researchers chose the media "Flannel Board" because it is claimed that this media is more appropriate for education in this era because of the application of creative teaching. The research method, namely: Identifying topics related to writing skills in learning Arabic and focusing on the "Flannel Board" learning media for teaching Arabic. The object of this research is the seventh grade students of SMP Bilingual Terpadu Krian Sidoarjo. in the 2015-2016 school year. The learning media "Flannel Board" is one of the visual aids in the form of a blackboard made of flannel to compose pictures and words related to educational materials. Flannel board is a learning media that makes it easier for teachers to deliver lessons, because with this media teachers can provide educational material in an interesting way with the aim of increasing the efficiency and effectiveness of student learning. and enthusiasm for student learning. because the creativity of teachers in managing learning is very influential on student learning outcomes.